Influência de causas: as potencialidades comunicativas do de YouTubers pertencentes a grupos minorizados socialmente e os impactos de sua influência em suas audiências - Melo, Sergio Henrique Teijido (2021)
Within a connected context, the dynamics of a celebrity culture take on different dimensions. Digital networks, by allowing not only large communication companies to have the possibility of reaching a massive audience, enabled new influencers/celebrities to be formed. This scenario ends up providing a space of speech for socially minoritized groups. It also makes it possible for members of these groups to reach, in a more representative way than in analogical contexts, a status of influencers inside and outside the minoritized groups. This work investigates the context of influencers of causes through a phenomenological study and individual interviews. And it identifies the main impacts they manage to have on their followers: the ordering of ideas and learning, empowerment and admiration.